Educação escolar indígena na região do Uaçá no município de Oiapoque-AP (1964-1985) - Bastos, Cecília (2014)
This thesis deals with education for Uaçá indigenous in the Oiapoque town, border between the state of Amapá and French Guiana, between 1964 and 1985. The research context refers to the time when the military government reshaped both indigenous policies as education legislation, measures that helped to implement a model of education for indigenous Palikur, Karipuna and Galibi-Maworno in the Oiapoque region. The objective was to understand how focusing on education and teaching in Brazil Indian policies were upheld, appropriate and practiced in schools Uaçá and how it was establishing a culture of education associated with the meaning of their own indigenous education. This education was conducted by various agents of the contact at the time of the military government, including the Indian Protection Service (SPI), National Indian Foundation (FUNAI), government of the Federal Territory of Amapá, Indigenous Missionary Council (CIMI) and the Summer Institute of Linguistics (SIL). The theoretical elements articulated to the concepts of schooling and indigenous education, cultural identity, and memory. These elements were important for the methodology of the research and the collection of documentary sources, configured from the notes of the classroom with students of Undergraduate Intercultural from the Federal University of Amapá (UNIFAP), of indigenous law and education at the time and documents found in many institutional collections (Diocesan Curia of the Church of São José de Macapá, Amapá Public Library, Nucleus of Indigenous Education of Education Department of Amapá (NEI-SED/AP), CIMI and FUNAI). From the theoretical discussion and analysis of these sources, we conclude that widespread education in indigenous schools had produced brands, rules, and customs, blending the very education of indigenous culture, marking a process of appropriation and redefinition of the school in the villages. This culture of education was marked by external culture and identity of the indigenous Uaçá devices involving a wide network of established relationships and resized by practices and standards built in school that served to keep the Indians in the Brazilian border, given the purposes of national security. But this also leads us to understand, in another perspective, that the school examined served as a place of reinvention of education in place of a differentiated culture. Finally, it is important to say that the thesis had as main objective, to point for the possibility of thinking in the present, education and the school in an indigenous area as a historically and culturally produced practice.